Evaluation and Comparison of the Quality of Two Crude Oils at Dura Oil Refinery - Al-Dahhan, Wedad H (Al-Nahrain Journal of Science, 2018)
Two types of crude oil at Dura oil refinery were selected and tested using the physical properties: Boiling point, Density, Pour point, Surface tension and Aniline point in addition to the calculated results: API gravity, Kw factor and Correlation index in order to determine the characteristics of oils and comparison between them. A special distillation curves were obtained according to ASTM-2892 distillation method for the tested crudes to calculate the percentages and quantities of each crude oil derivatives to support the preliminary data of the physical properties to indicate the characteristics in terms of being paraffinic, naphthenic or aromatic as an addition comparison between crude oils used. It turned out through the entire results that the properties of crude oil (A) shows that it is heavier and the greater the concentration of naphthenes and aromatics than in the crude oil (B) and the same concept, the (B) more paraffinic than (A).